Prevalence of periodontal disease in Radiology Installation of RSGMP Hasanuddin University Makassar after the Covid-19 pandemic in 2022: Prevalence of periodontal disease in Radiology Installation of RSGMP Hasanuddin University Makassar after the Covid-19 pandemic in 2022 - Kintara Putri Amriana Sahidu; Barunawaty Yunus (Makassar Dental Journal, 2024)
Periodontal disease is a disease caused by damage to the tooth supporting tissue starting from inflammation of the gingiva which is reversible and then gets worse until there is loss of tooth supporting tissue and periodontitis. During the Covid-19 pandemic, people were encouraged to postpone dental treatment or not come to the dentist's office. It was found that an increased inflam-matory response as a result of SARS-CoV-2 infection could trigger periodontitis and this is because the presence of periodontal disease is a predisposing factor for Covid-19. Descriptive observational study through panoramic and periapical radiographic data in March-September 2022, then the results were entered into distribution tables and graphs. Periodontal disease was found to be most prevalent in males. Based on age, most occurred in the adult age group, and the most common periodontal disease found was chronic periodontitis which occurred mostly in men. It is concluded that the prevalence of periodontal disease in RSGMP Universitas Hasanuddin Makassar after the pandemic is high due to people who are still not free to go to the dentist as an effort to prevent the spread of Covid-19.